Improving oral health in nursing home residents: A process evaluation of a shared oral care intervention. Issue 17 (24th June 2020) - Aagaard, Karin; Meléndez‐Torres, G. J.; Overgaard, Charlotte
Abstract: Aims and objectives: To evaluate the process of implementing an oral care intervention in nursing homes in a Danish municipality. Background: Older people with aged natural dentition require preventive and curative oral health care. An intervention based on principles of situated learning was implemented to establish closer cooperation between dental and nursing staff in nursing homes, leading to improved oral hygiene in nursing home residents. Design: An embedded multiple‐case study combined with principles of realist evaluation unfolded in three phases: Formulation of initial programme theory, Testing and Refining the programme theory. The COREQ checklist is followed in reporting. Methods: Observations, six group interviews and 22 face‐to‐face interviews with dentists, dental practitioners, nursing home managers, care professionals and residents were conducted in three nursing homes ( n  = 41). Results: Three main outcomes of a programme theory were identified, relating to (a) residents, in the form of new oral care routines; (b) interdisciplinary working, in the form of professional pride in performing sufficient oral care; (c) organisational level changes, in the form of increased interdisciplinary knowledge sharing. The overarching supportive mechanisms were the creation of relationships between residents, dental practitioners and care professionals as well as nursing home management taking responsibility for structure, planning and knowledge sharing. Conclusion: The situated learning perspective supported residents and care professionals' competencies in performing sufficient oral care. The shared oral care intervention supports an individual and multidisciplinary assessment of nursing home residents' ability to self‐care concerning oral care. Contextual factors, supportive and restraining mechanisms influence the intervention's success. Relevance to clinical practice: Understanding the complexity within interdisciplinary cooperation in primary nursing and unravelling the necessary properties to enhance nursing home residents' oral health care are areas of improvement for care service in nursing homes.